2009
DOI: 10.1029/2008jd010870
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of boreal region biomass burning aerosols in central Alaska and seasonal variation of aerosol optical depth at an Arctic coastal site

Abstract: [1] Long-term monitoring of aerosol optical properties at a boreal forest AERONET site in interior Alaska was performed from 1994 through 2008 (excluding winter). Large interannual variability was observed, with some years showing near background aerosol optical depth (AOD) levels (<0.1 at 500 nm) while 2004 and 2005 had August monthly means similar in magnitude to peak months at major tropical biomass burning regions. Single scattering albedo (w 0 ; 440 nm) at the boreal forest site ranged from $0.91 to 0.99 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
164
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(198 citation statements)
references
References 58 publications
(89 reference statements)
31
164
3
Order By: Relevance
“…These OC and BC emissions are mostly from boreal forest fires, OC/BC ratios from boreal forest fires are higher than from extratropical vegetation fires (e.g Andreae and Merlet, 2001). The imaginary refractive index of the Alaska smoke observations, analyzed by Eck et al (2009), showed low values implying small BC fraction, and a very large relative increase towards lower wavelengths, likely resulting from enhanced absorption by OC, which is evident also in our retrievals. From the biomass burning sites, Alta Floresta exhibits somewhat larger OC/BC ratio than Mongu.…”
Section: Resultssupporting
confidence: 56%
“…These OC and BC emissions are mostly from boreal forest fires, OC/BC ratios from boreal forest fires are higher than from extratropical vegetation fires (e.g Andreae and Merlet, 2001). The imaginary refractive index of the Alaska smoke observations, analyzed by Eck et al (2009), showed low values implying small BC fraction, and a very large relative increase towards lower wavelengths, likely resulting from enhanced absorption by OC, which is evident also in our retrievals. From the biomass burning sites, Alta Floresta exhibits somewhat larger OC/BC ratio than Mongu.…”
Section: Resultssupporting
confidence: 56%
“…Very low imaginary parts of the refractive index (IRI) with values form 0.0012 to 0.003 compared to 0.0094 ± 0.003, given by Dubovik et al (2002), and single scattering albedos close to 1 indicate a weak absorption by the particles, and therefore a low black carbon fraction, in disagreement with some previous works about biomass burning particles Alados-Arboledas et al, 2011) but in agreement with others (Eck et al, 2009;Samaras et al, 2015). The spectral dependence of the SSA between 355 and 532 nm shows what could be considered an anomalous behavior compared to some columnar retrievals (Reid et al, 2005a, b;Dubovik et al, 2002), where biomass burning aerosol SSA typically decreases with increasing measurement wavelength.…”
Section: Microphysical Propertiescontrasting
confidence: 55%
“…The spectral dependence of the SSA between 355 and 532 nm shows what could be considered an anomalous behavior compared to some columnar retrievals (Reid et al, 2005a, b;Dubovik et al, 2002), where biomass burning aerosol SSA typically decreases with increasing measurement wavelength. However, the nearly constant or slightly positive spectral dependence is also found in other studies (Eck et al, 2009;Alados-Arboledas et al, 2011;Pereira et al, 2014). It is noteworthy, that the refractive index is as- Table 4.…”
Section: Microphysical Propertiesmentioning
confidence: 63%
“…Second, we do not know whether the tuning of the algorithm for the Indonesian region will hold for other situations of heavy smoke from wildfires. The Indonesian smoke proved to be relatively non-absorbing, which might be similar to smoke from peat burnings in other places 20 such as those from Alaskan fires in summer of 2004and 2005(Eck et al, 2009), but may be inappropriate for more absorbing smoke in other places and situations. Third, there is also a philosophical question of how fragmented should a global aerosol retrieval become?…”
Section: Discussionmentioning
confidence: 99%